Komunikasi Interpersonal pada Proses Ta’aruf Melalui Aplikasi Ta’aruf Online Indonesia - Rizka Rahmawati; Lintang Ratri Rahmiaji (Interaksi Online, 2022)
Technological changes in the new era encourage ta'aruf to transform into a process of getting acquainted using media, or online ta'aruf. How interpersonal relationships are built in media intermediaries and thirdparty admins can work. This study aims to determine how the description of the interpersonal communication process in the development of partner relationships through the Ta'aruf Online Indonesia application. The phenomenon of online ta'aruf is interesting to study in the framework of the development of information technology and the concept of relationships in Islamic rules. The theory used is the theory of uncertainty reduction, violation of expectations, and the concept of ta'aruf. This research uses descriptive exploratory method. The subjects in this study were users of the Ta'aruf Online application who had been married for the last one year. Data collection methods in this study used observation, interviews and documentation with data analysis techniques including data reduction, data display, and conclusion drawing/verification. The results of the study show that Ta'aruf in the digital era has changed, namely to become ta'aruf through online or online applications. Ta'aruf online at Ta'aruf Online Indonesia was chosen by the informant because it was considered the most in accordance with Islamic rules. Compared to offline ta’aruf, there are two substantive differences, namely the limited function of intermediaries, and freedom as well as diversity of choice. The online ta'aruf communication process has almost the same stages as offline ta'aruf, usually starting with a premarital (school) study, registering and activating a TOI account, filling out a CV, applying for ta'aruf, asking questions, nadzor and khitbah. The deciding point is in the question and answer process and whether it is able to reduce uncertainty and meet expectations. The success of the online ta'aruf communication process through Indonesia's online ta'aruf has the potential for success when the prospective partner has strong motivation, parental approval, ideological similarity, willingness to understand the partner, and consideration of the prospective partner's faith.